2008
DOI: 10.1101/gad.1706908
|View full text |Cite
|
Sign up to set email alerts
|

Closing the circadian negative feedback loop: FRQ-dependent clearance of WC-1 from the nucleus

Abstract: In Neurospora crassa, a transcription factor, WCC, activates the transcription of frq. FRQ forms homodimers as well as complexes with an RNA helicase, FRH, and the WCC, and translocates into the nucleus to inactivate the WCC, closing the time-delayed negative feedback loop. The detailed mechanism for closing this loop, however, remains incompletely understood. In particular within the nucleus, the low amount of FRQ compared with that of WC-1 creates a conundrum: How can the nuclear FRQ inactivate the larger am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
78
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(82 citation statements)
references
References 36 publications
(65 reference statements)
3
78
0
1
Order By: Relevance
“…fragmented free-running behavior [103,104], supporting the critical role of Rev-erbs in generating robust rhythms. Furthermore, just as the slower additional NFL is more effective in PS models [59], the half-lives of activators are also considerably longer than those of repressors in mammals [121][122][123][124][125], Drosophila [126,127] and Neurospora [76]. Tight regulation of activator level via an additional NFL (Fig.…”
Section: Robust Designs Of Interlocked Transcriptional Feedback Loopsmentioning
confidence: 99%
“…fragmented free-running behavior [103,104], supporting the critical role of Rev-erbs in generating robust rhythms. Furthermore, just as the slower additional NFL is more effective in PS models [59], the half-lives of activators are also considerably longer than those of repressors in mammals [121][122][123][124][125], Drosophila [126,127] and Neurospora [76]. Tight regulation of activator level via an additional NFL (Fig.…”
Section: Robust Designs Of Interlocked Transcriptional Feedback Loopsmentioning
confidence: 99%
“…FRQ-FRH inhibits frq expression through a direct interaction with WCC that is mediated by WC-2 (7,8). FRQ undergoes phase-specific phosphorylation over the course of the day, and this phosphorylation controls regulated transport between the nucleus and cytoplasm, destabilization, and turnover (9)(10)(11)(12). In addition, there appears to be fine-tuned control of chromatin in both the activation and feedback inhibition phases of circadian oscillations (13)(14)(15)(16)(17).…”
Section: Dna Methylationmentioning
confidence: 99%
“…In light, VVD forms a rapidly exchanging dimer in solution, suggesting the possibility that the LOV domain of VVD could interact with other PAS domains, including those found in the WCC proteins (28)(29)(30). Cell fractionation studies have shown VVD to be exclusively localized in the cytosol (9), whereas most of the WCC is nuclear (9)(10)(11)(12), raising the question of how VVD communicates with the WCC to affect various WCC-mediated activities.…”
mentioning
confidence: 99%
“…The WHITE COLLAR (WC)-1 and WC-2 proteins control most light responses in Neurospora (7,8). WC-1, mainly localized in the nucleus (9)(10)(11)(12), is both a FAD-binding photoreceptor and a GATA zinc finger transcription factor (13,14). Through their PER-ARNT-SIM (PAS) domains (15)(16)(17), WC-1 and WC-2, another GATA zinc finger transcription factor, form the white collar complex (WCC).…”
mentioning
confidence: 99%